PENGARUH MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MODERASI - Dinda Indira Subagio (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2022)
The purpose of this study is to analyze the effect of intellectual capital and firm value on the consumer goods industry listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2020. The second objective is to analyze the moderating effect of earnings management on the relationship between intellectual capital and firm value. Based on purposive sampling criteria, a sample of 153 consumer goods industry companies was obtained during 2018-2020. The secondary data used is in the form of panel data in the form of time series data for 2018 - 2020 and cross sections. A quantitative approach is used in this study, with multiple linear regression analysis using the Eviews11 (Econometrics and Statistics Software) program. The best estimation model used in this study is the Random Effect Model (REM). The results of the regression test conducted with a significance level of 5% prove that intellectual capital has a significant positive effect on firm value, and earnings management significantly reduces the influence of intellectual capital on firm value. This study provides information on the effectiveness of the application of intellectual capital and adds empirical evidence related to earnings management as a moderating variable.